Formation of the Polish Pastoral Care structures within the borders of contemporary Germany - NECEL, WOJCIECH (Prawo Kanoniczne, 2014)
Based on the migration of the people of the Polish origin to Germany author presents origin and development of the structuers of the Polish Pastoral Care in Germany. Proposed study in the view of the author is nessesary to understand novadays character of the apostolate for Poles in Germany, which base in its structures on recomendations containd in the instraction Erga migrantes caritas Christi.